High 17-hydroxyprogesterone level in newborn screening test for congenital adrenal hyperplasia - Levy-Shraga, Yael (BMJ Case Rep, 2016)
We report a case of a female infant with an elevated 17-hydroxyprogesterone level detected in the newborn screening for 21-hydroxylase deficiency, the most common cause of congenital adrenal hyperplasia. The physical examination was unremarkable including no dysmorphism and no signs of virilisation. In the absence of clinical evidence of androgen excess, as would be expected in a female infant with 21-hydroxylase deficiency, further evaluation was performed and led to the diagnosis of the extremely rare disorder, 3β-hydroxysteroid dehydrogenase deficiency. This case highlights the differential diagnosis of elevated 17-hydroxyprogesterone levels in newborn screening and the importance of correct diagnosis for improving patient care.